2019
DOI: 10.1016/j.atherosclerosis.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Apabetalone downregulates factors and pathways associated with vascular calcification

Abstract: and extraterminal (BET) proteins are implicated in VSMC transdifferentiation and calcification. • Apabetalone, a BET inhibitor, prevents calcification of VSMCs by regulating expression of key factors. • BET protein BRD4 may cooperate with 7 specific transcription factors (TFs) to promote transdifferentiation and calcification. • Apabetalone is a promising therapeutic for pathological vascular calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 59 publications
1
53
0
Order By: Relevance
“…RVX-208 reduces the expression of complement factors either in vitro or in mice and in CVD patients [189]. RVX-208 counters the trans-differentiation and calcification of VSMCs [190]. RVX-208 lowers serum alkaline phosphatase levels and improves CVD risk [191].…”
Section: Rvx-208 (Apabetalone)mentioning
confidence: 99%
“…RVX-208 reduces the expression of complement factors either in vitro or in mice and in CVD patients [189]. RVX-208 counters the trans-differentiation and calcification of VSMCs [190]. RVX-208 lowers serum alkaline phosphatase levels and improves CVD risk [191].…”
Section: Rvx-208 (Apabetalone)mentioning
confidence: 99%
“…Vascular calcification (VC) is prevalent in coronary artery disease, and its extent predicts cardiovascular risk [1]. Causes of calcification in atherosclerosis include dysregulated matrix metabolism, epitaxial mineral deposition, inflammation, oxidative stress, and apoptosis [2].…”
Section: Introductionmentioning
confidence: 99%
“…After screening through 224 articles, we identified 66 original reports examining epigenetic processes in VC ( Figure 1). Interestingly, most reports (n = 40; 60.6%) looked into the pathogenic role of non-coding RNA in VC, while histone modification (n = 6; 9.1%) [53][54][55][56][57][58], DNA methylation (n = 8; 12.1%) [5,[59][60][61][62][63][64][65], and chromatin changes (n = 3; 4.5%) [66][67][68] accounted for one-fourth only. Nine (13.6%) [69][70][71][72][73][74][75][76][77] examined the discrepancy of epigenetic signatures between subjects or animals with and without VC but not their pathogenic influences.…”
Section: Strategy Of Literature Review and Findingsmentioning
confidence: 99%
“…SMARCA, a chromatin remodeler influencing chromatin structure and gene expression, has been shown to increase significantly in calcified rat aortas compared to non-calcified ones, and SMARCA upregulation might contribute to aberrant levels of VC-regulating miRNAs [68]. Gilham and colleagues demonstrated that molecules inhibiting chromatin modification site readers such as BET protein might help improve VC, but the findings were limited to in vitro only [67]. Although results from these three studies lend support to the notion that chromatin changes can be a unique signature of VC and even be pathogenic and druggable, more mechanistic research is expected to shed light on the specificity and the efficacy of such chromatin-oriented interventions for VC.…”
Section: Chromatin Changes In Vcmentioning
confidence: 99%